2017
DOI: 10.1016/j.gaitpost.2017.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of center of pressure measures for assessing the development of sitting postural control through the stages of sitting

Abstract: Cerebral palsy (CP) impairs an individual’s ability to move and control one’s posture. Unfortunately, the signs and symptoms of CP may not be apparent before age two. Evaluating sitting posture is a potential way to assess the developing mechanisms that contribute to CP. The purpose of this project was to determine the reliability of linear and nonlinear measures, including inter- and intrastage reliability, when used to analyze the center of pressure (COP) time series during the stages of sitting development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The MLE is based on the Lyapunov's theory of dynamic stability, initially formulated to assess the sensitivity of a mechanical system to small perturbations and is often used to quantify how the patterns of gait kinematics change in response to small perturbations 7,11 . While arguments can be made for any of the deriving stability measures, recent reviews suggested the use of the MLE as a prominent measure of dynamic stability 32,38,39 and has thus received extensive focus in the recent years [138][139][140][141][142][143]39,144,145 .…”
Section: Introductionmentioning
confidence: 99%
“…The MLE is based on the Lyapunov's theory of dynamic stability, initially formulated to assess the sensitivity of a mechanical system to small perturbations and is often used to quantify how the patterns of gait kinematics change in response to small perturbations 7,11 . While arguments can be made for any of the deriving stability measures, recent reviews suggested the use of the MLE as a prominent measure of dynamic stability 32,38,39 and has thus received extensive focus in the recent years [138][139][140][141][142][143]39,144,145 .…”
Section: Introductionmentioning
confidence: 99%
“…19 It is very important in almost every movement and is sometimes referred to as postural control, which includes the ability to maintain body balance in the force of gravity by keeping the center of body weight in the same position. 20 Balance is supported by components controlling balance including sensory information systems, synergistic postural muscle responses, muscle strength, adaptation systems, and joint range of motion. 21 Most subjects have excellent, good, and moderate levels of static balance and excellent, good, and sufficient levels of leg muscle strength.…”
Section: Methodsmentioning
confidence: 99%

The relationship between leg muscle strength and static balance in surfers

Cokorda Istri Ajeng Prameswari,
I Dewa Gede Alit Kamayoga,
I Gusti Ayu Artini
et al. 2024
ptji
“…Bishop, Hillier and Thewlis [28] examined the intra-rater agreement and the inter-rater agreement of the Adelaide in-shoe foot model in two separate series of patients. Wickstrom, Stergiou and Kyvelidou [29] examined the reliability of centre of pressure measures in infants through the stages of sitting. Cheng et al [30] examined the intra-and inter-observer reliability of radiographic measurements as part of a study on compensatory mechanisms in the pelvis and lower extremities in patients with pelvic incidence and lumbar lordosis mismatch.…”
Section: Intraclass Correlation Coefficients Levels Of Agreement Andmentioning
confidence: 99%